Regioselective Nucleophilic Substitution of 5‐Bromo‐2‐methoxytropone. Issue 6 (28th June 2014) - Sato, Ohki; Nitta, Ai; Yamamoto, Ami
ABSTRACT The reaction of 5‐bromo‐2‐methoxytropone with O‐ and N‐nucleophiles, such as ethanol/potassium carbonate, sodium hydroxide, diethylamine, propylamine, p‐chloroaniline/triethylamine, and p‐phenylenediamine/triethylamine, gave corresponding 2‐O‐ and 2‐N‐substituted troponoids. Alkyl diamines reacted with the substrate to produce bis(2‐aminotropone)s. In the case of S‐nucleophiles as 1‐propanethiol, thiophenol, and 4‐aminothiophenol with a base, the regioselective substitution at the 5‐position occurred. Halogenation reagents, triphenyldibromophosphorane and its dichloro analogue, furnished 2, 5‐dibromo‐ and 2, 5‐dichlorotropones, respectively.